The Interdisciplinary Approach and It’s Contribution to the Study of Living Hadith : Pendekatan Interdisipliner dan Kontribusinya dalam Studi Living Hadis - Junianto, Viki; Mo’afi; Amrulloh (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The term